Cropping System Intensification as a Management Method Against Vectors of Viruses Causing Maize Lethal Necrosis Disease in Kenya. Issue 2 (2nd October 2017) - Namikoye, E. S.; Kariuki, G. M.; Kinyua, Z. M.; Githendu, M. W.; Kasina, M.
ABSTRACT: Maize Lethal Necrosis Disease (MLND) has emerged as a great threat to maize production in East Africa. It is caused by a synergistic infection of maize by sugarcane mosaic virus (SCMV) and maize chlorotic mottle virus (MCMV). This study was carried out in Bomet County, Kenya, to determine the potential of various cropping systems to manage vectors of MLND–causing viruses. Plots measuring 7.5  m × 5.25  m were planted with maize ( Zea mays L.) intercropped or bordered by elephant grass ( Pennisetum purpureum Schumach.), coriander ( Coriandrum sativum L.), pearl millet ( Pennisetum glaucum (L.) R. Br . ) and Gadam sorghum ( Sorghum bicolour (L.) Moench). Maize monoculture was used as a control treatment; the nine treatments were arranged in a randomized complete block design and replicated four times for two seasons (December 2014 to April 2015 and April 2015 to September 2015). Data on corn thrips and corn leaf aphid infestation, MLND severity and incidence, MCMV and SCMV viral load, and yield were recorded. The sorghum border was the only companion crop that tested positive for MCMV and none tested positive for SCMV. Maize intercropped with elephant grass had significantly ( P <  0.01) the least incidence of disease. However, this treatment produced significantly lower yields ( P <  0.01). Coriander was the only companion plant most preferred by both corn thrips and corn leaf aphids ( P <  0.001). Maize from all cropping systems tested positive for MCMV ( P <  0.001) while maize grown with coriander tested negative for SCMV ( P <  0.001). Yields from plots surrounded by sorghum and coriander were significantly similar to those from maize monoculture plots. These findings suggest that maize should be intercropped with coriander due to its potential to trap corn leaf aphids and protect maize from SCMV. In addition maize should be grown surrounded by a sorghum border to maximize yield in areas where MLND is prevalent.